Cataract Surgery in Dry Eye Disease: Visual Outcomes and Complications - Donthineni, Pragnya R.; Das, Anthony V.; Shanbhag, Swapna S.; Basu, Sayan (Frontiers in Medicine, 2020)
Purpose: To describe the visual outcomes and complications following cataract surgery in dry eye disease (DED) Methods: This retrospective study included 668 eyes of 399 patients with DED, who underwent cataract surgery between 2011 and 2019 at our multi-tier ophthalmology hospital network. Based on etiology, they were divided into three groups: cicatrizing conjunctivitis (CC), meibomian gland dysfunction (MGD), and Sjogren’s syndrome (SS). The data on demographics, visual impairment, surgical technique, visual outcomes, and complications were collected using an electronic medical record system. Median LogMAR best corrected visual acuity (BCVA) with interquartile range (IQR) was compared using Wilcoxon’s rank-sum test. Results: The median age at which cataract surgery was performed was 58(IQR: 47-65) years. Etiology of DED was CC in 279, MGD in 255, and SS in 134 eyes. Most (471) eyes underwent phacoemulsification, under peribulbar anesthesia (548) through temporal clear corneal incision (209) with foldable intraocular lens implantation (417). The overall median LogMAR BCVA improved from 1.1(IQR: 0.6-2.1) at baseline to 0.3(IQR: 0.1-0.7) and 0.1(IQR: 0-0.65) at 1 and 6-weeks (P<0.0001) post-operatively. The median 6-week postoperative BCVA was 0.3, 0.1 and 0.1 in CC, MGD and SS respectively, and significantly better than at baseline(P<0.0001). The leading cause of sub-optimal vision was corneal scarring (44; 9%) and the commonest complication was posterior capsular rupture with vitreous loss (23;3%). Conclusion: Cataract surgery has good visual outcomes in patients with DED, without any disconcerting rate of complications. Pre-existing keratopathy is the main determinant of the extent of postoperative visual recovery.